Is healthcare a ‘Necessity’ or ‘Luxury’? an empirical evidence from public and private sector analyses of South-East Asian countries? - AM Khan, Jahangir; Alam Mahumud, Rashidul (© 2015 Springer Verlag, 2017)
This article was published in Health Economics Review [© 2015 Springer Verlag] and the definite version is available at: http://link.springer.com/article/10.1186/s13561-014-0038-y